Machine translation engines and their use as a lexicographic tool to translate self-contained lexical units - Maldonado González, María Concepción; Liébana González, María (Círculo de Lingüística Aplicada a la Comunicación, 2021)
This paper provides a review of some machine translation (MT) systems, as well as the most common problems we encounter when using machine translation to translate self-contained lexical units out of context.The focus is to identify the limitations of linguistic MT engines and to consider whether it is necessary to incorporate lexicographic data into these systems, to improve their performance. To this end, we will take a practical approach and use Google Translator, Bing Microsoft Translator and DeepL to translate self-contained lexical units. We will then evaluate their performance by comparing the results with those we would have obtained had we consulted bilingual dictionaries for the same tasks. We will conclude that the quality of the output generated by MT engines is not sufficiently accurate; in general, the lexicographic data found in many bilingual dictionaries online provides more precise and comprehensive lexicographic information to satisfy the user's communicative needs
Keywords: Translation; translation tools; electronic lexicography; bilingual dictionaries